2008
DOI: 10.1038/nm1787
|View full text |Cite
|
Sign up to set email alerts
|

Activation of PDGF-CC by tissue plasminogen activator impairs blood-brain barrier integrity during ischemic stroke

Abstract: LRP1 in the NVU to promote tPA-mediated activation of PDGF-CC. Mac-1-deficient mice (Mac-1 −/−) are protected from tPA-induced BBB permeability but not from perme-ability induced by intracerebroventricular injection of active PDGF-CC. Immunofluorescence analysis demonstrates that Mac-1, LRP1, and the PDGFRα all localize to the NVU of arterioles, and following middle cerebral artery occlusion (MCAO) Mac-1 −/− mice show significantly less PDGFRα phosphorylation, BBB permeability, and infarct volume compared to w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

40
500
4
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 404 publications
(546 citation statements)
references
References 46 publications
40
500
4
2
Order By: Relevance
“…Altogether, these events were associated with detachment of astrocytic end-feet from the basal lamina and subsequent increased BBB permeability (Polavarapu et al, 2007). In addition, it has been reported that rtPA could mediate the local activation of latent platelet-derived growth factor-CC (PDGF-CC) and subsequent activation of PDGF-a receptors on pericytes after cerebral ischemia (Macrez et al, 2011a, b), an effect leading to hemorrhagic transformation (Su et al, 2008). Indeed, intraventricular injection of rtPA or active PDGF-CC, in the absence of ischemia, led to significant increase in BBB permeability.…”
Section: Tissue-type Plasminogen Activator At the Blood-brain Barriermentioning
confidence: 99%
“…Altogether, these events were associated with detachment of astrocytic end-feet from the basal lamina and subsequent increased BBB permeability (Polavarapu et al, 2007). In addition, it has been reported that rtPA could mediate the local activation of latent platelet-derived growth factor-CC (PDGF-CC) and subsequent activation of PDGF-a receptors on pericytes after cerebral ischemia (Macrez et al, 2011a, b), an effect leading to hemorrhagic transformation (Su et al, 2008). Indeed, intraventricular injection of rtPA or active PDGF-CC, in the absence of ischemia, led to significant increase in BBB permeability.…”
Section: Tissue-type Plasminogen Activator At the Blood-brain Barriermentioning
confidence: 99%
“…PDGFA is observed to be involved in atherosclerotic stroke previously (Xu et al, 2008). PDGF signaling is also reported to regulate blood-brain barrier permeability and integrity during ischemic stroke (Su et al, 2008). EGF has been shown to be implicated in neurogenesis and neuroprotection.…”
Section: Discussionmentioning
confidence: 99%
“…Both PDGFRa, a factor associated with perivascular astrocytes [38] and shown to be involved in glial-endothelial cell interactions and critical for maintenance of the BBB [38], and musashi, which is an RNA-binding protein that is highly specific for neural stem cells [23] and is not expressed in fully differentiated cells [26], were assessed in the claudin 5 + cells. FACS analysis showed that PDGFRa was expressed on these cells (Fig.…”
Section: Claudinmentioning
confidence: 99%